1999
DOI: 10.1016/s0020-7292(98)00217-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired antioxidant activity in women with pre‐eclampsia

Abstract: In women with pre-eclampsia, sera antioxidant activity and antioxidant level of plasma are decreased when compared with normotensive pregnancies. Impaired antioxidant activity and the reduction of antioxidant levels which increase the level of lipid peroxidation products may cause peroxidative damage of vascular endothelium and result in clinical symptoms of pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 14 publications
2
49
2
4
Order By: Relevance
“…After a further 30 years, Mikhail et al (1994) reported that plasma levels of reduced ascorbic acid are markedly decreased in patients with mild and severe preeclampsia. The association between decreased ascorbate and pre-eclampsia has been confirmed by several other studies (Hubel et al 1997;Sagol et al 1999;Panburana et al 2000;Chappell et al 2002a;Llurba et al 2004).…”
Section: The Maternal Circulation and Oxidative Stresssupporting
confidence: 54%
“…After a further 30 years, Mikhail et al (1994) reported that plasma levels of reduced ascorbic acid are markedly decreased in patients with mild and severe preeclampsia. The association between decreased ascorbate and pre-eclampsia has been confirmed by several other studies (Hubel et al 1997;Sagol et al 1999;Panburana et al 2000;Chappell et al 2002a;Llurba et al 2004).…”
Section: The Maternal Circulation and Oxidative Stresssupporting
confidence: 54%
“…Antioxidants, due to their ability to scavenge free radicals, have been postulated to protect endothelial cell membranes against free radical-induced damage in preeclampsia [3][4][5]. There is evidence of a deficiency in protective antioxidant systems or increased utilization of antioxidants in preeclamptic compared with normal pregnancies [5,6]. Previous studies of plasma antioxidants in preeclampsia have primarily focused on carotenoids, vitamin E, vitamin C, thiols and sera antioxidant activity [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of a deficiency in protective antioxidant systems or increased utilization of antioxidants in preeclamptic compared with normal pregnancies [5,6]. Previous studies of plasma antioxidants in preeclampsia have primarily focused on carotenoids, vitamin E, vitamin C, thiols and sera antioxidant activity [6][7][8][9][10]. Supplementation with vitamins E and C in women at risk of preeclampsia showed significant beneficial effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pre eclampsia is a major contributor to premature births and intrauterine growth restriction. 13 The concentrations of Malondialdehyde (MDA) in Pregnancy induced hypertensive cases were significantly elevated in comparison with controls (p < 0.001) in maternal blood due to increased placental production of lipid peroxides. Lipid Peroxidation results in primary lipid Peroxidation products such as lipid hydro peroxides and secondary products such as malondialdehyde and lipid peroxides Plasma triglycerides in maternal blood in Pregnancy induced Hypertension were significantly higher than the control values (p < 0.001) Plasma Total Cholesterol in maternal blood shows a significant rise in Pregnancy induced hypertension cases against control (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%